Safety and immunogenicity of 15-valent pneumococcal conjugate vaccine compared to 13-valent pneumococcal conjugate vaccine in adults ≥65 years of age previously vaccinated with 23-valent pneumococcal polysaccharide vaccine. Issue 3 (4th March 2019) - Peterson, James T.; Stacey, Helen L.; MacNair, John E.; Li, Jianing; Hartzel, Jonathan S.; Sterling, Tina M.; Benner, Patrice; Tamms, Gretchen M.; Musey, Luwy K.
ABSTRACT: Background : Pneumococcal disease remains a public health priority in adults. Previous studies have suggested that administration of pneumococcal polysaccharide vaccine or pneumococcal conjugate vaccine within three years following receipt of PPV23 was associated with increased reactogenicity and reduced antibody titers in comparison to longer intervals. Safety and immunogenicity of 15-valent pneumococcal conjugate vaccine (PCV15) was evaluated in adults ≥ 65 years of age with prior history of PPV23 vaccination (V114-007; NCT02573181). Methods : A total of 250 adults who received PPV23 at least 1 year prior to study entry received a single dose of either PCV15 or PCV13 (125/arm) and were followed for safety for 14 days postvaccination. Serotype-specific Immunoglobulin G (IgG) geometric mean concentrations (GMCs) and opsonophagocytic activity (OPA) geometric mean titers (GMTs) were measured immediately prior and 30 days postvaccination. Results : Safety profiles were comparable between PCV15 and PCV13 recipients. Following vaccination, serotype-specific antibody responses for the 13 shared serotypes were generally comparable between recipients of PCV15 and PCV13 for IgG GMCs, OPA GMTs, and geometric mean fold rises (GMFRs) and percentages of subjects with ≥ 4-fold-rise from baseline for both IgG and OPA. Recipients of PCV15 had numerically higher antibody responses than PCV13 for two serotypes unique to PCV15 (22F, 33F). Conclusion : PCV15 was generally well tolerated and induced high levels of IgG and OPA antibodies to all 15 serotypes included in the vaccine when given as a single dose to adults ≥ 65 years of age previously vaccinated with PPV23.